Kajian perancangan gunatanah kawasan sumber makanan negara - Zainal, Megat Sahrir; Abidin, Suriani; Juraimi, Abdul Shukor; Esa, Yuzine; Samsudin, Anjas Asmara; Asmawi, M. Zainora; Yahya, Mohammad Zaki; Sulaiman, Muhammad Firdaus; Razak, Khamarrul Azahari; Shamsudin, Mad Nasir; Mohd Saad, Nor Shah; Razak, Mohd Zainal; et al. (PLANMALAYSIA, 2021)
The agriculture sector contributes to the economic growth of the nation, covering not only agriculture but also fisheries and livestock. More importantly, the agriculture sector is crucial in relation to its importance of food security. Thus, the inception report of the study will lead towards the data analysis before coming out with its conclusive proposals in the forms of guidelines, initiatives and development control. The main sector namely land use will become the catalyst of the spatial analysis that will support the others sectors, such as infrastructure, environment, governance and others.